Retaining Quality Employees Through Career Development And Perceived Supervisor Support - Roslee, Azura; Abdullah Effendi, Azura (2016)
This conceptual paper highlights the importance of perceived supervisor support in the relationship between employee career development and their intention to turnover. Career development should both cater to individual employees as well as meet the needs of the organization. It could serve as an important link to reducing turnover among employees in the initial stages of their career, but perceived supervisor support could possibly enhance the retention of quality employees among them. Upon review of related literature, this study suggests that career development is mediated by perceived supervisor support to reduce turnover intention. Additionally, it proposes that gender and race, by way of representative bias, shape employees’ perceptions of supervisor support. This argument is sustained by the growing body of research concluding that supervisor-related perceptions can shape organization-related perceptions. The theoretical and practical significance and implications of perceived supervisor support are also discussed.